Evaluating the influence of economic aid and land ownership on the reduction in coffee yield and its socioeconomic consequences: A case study of the Akuapem North Municipality, Ghana. - Mohammed, Adams Latif; Cobbinah, Joseph; Addai, Frank (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Coffee is a highly valuable tropical agricultural commodity and is the second most traded commodity in the international market after oil. Despite coffee being cultivated in Ghana since the late 18th century, around the same time as cocoa was introduced, cocoa has become the more dominant crop due to coffee's low yield in Ghana. As a result, many farmers have shifted their focus from coffee farming to other crops, particularly cocoa, as it has become the country's primary source of foreign exchange. The purpose of the research was to investigate the impact of the reduction in coffee production on the livelihoods of farmers in the Akuapem North Municipality in the Eastern Region. The study aimed to identify the reasons behind the decline in coffee production as perceived by the farmers, as well as to determine their views on potential solutions to the problem. The purposeful sampling method was used to select two (2) communities, namely Apirede and Tinkong, based on the intensive production of coffee in the municipality. The snowball sampling method was used to select 50 respondents from the two communities. The results showed that most (92%) respondents were males, while the remaining 8% were females, which means a lot of males are into coffee production in the district. The majority (24%) identified inadequate financial assistance from the government and other financial sources as the major cause of the decline in coffee production. The majority (26% each) chose financial assistance from the government and access to credit as a way to improve coffee production. The majority (94%) of the respondents indicated that the decline in coffee production has affected their income. The study established that the government, NGO's, and other financial institutions such as banks or credit institutions in Akuapem North Municipality must take responsibility for granting loans or credit to farmers to address problems of finance encountered in their search to maximize the economic returns of the coffee industry. In addition, the government could also help coffee farmers acquire vast arable lands through clearly defined tenure rights and agreements for land owners and coffee farmers in the Akuapem North Municipality.